Managing change with integrity in Malaysian institution of higher education - Abu Samah, Siti Akmar; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
Change is a perennial buzzword in today’s world. In every facet of life that all of us undergo, will constantly and consistently meet the condition of change. When it happens, this chain of action will attract reaction of various multitudes which could either be desirable or undesirable. With every noble intention, change is supposed to improve, enhance and upgrade the aspects of living so that everyone in the organisation will benefit for its very existence. In the educational institution, the members in the organization inevitably face the challenges, be those imposed or designed, must learn to adapt or adopt to meet the demand. Change that takes place within as well as outside the institution can culminate mixed reception and perception among the clients. This paper attempts to explore the issues of integrity and the challenges that educational institution like that of Universiti Teknologi MARA faces in managing change.